Assessing Watershed Characteristics and Hydrological Response Using SWAT: A Case Study in the Raya Watershed, West Kalimantan - Alhakim, Euis Etty; Bondan, Abimanyu; Iswanto, Eko Rudi; Anzhar, Kurnia; Indrawati, Yuni; Solihat, Sufiana; Setiawan, Muhammad Anggri (BRIN Publishing, 2025)
The watershed is primarily influenced by land use and population activities within the watershed area. Along with the increasing number of people, there is the potential for land-use changes that lead to a change in the land's function. This condition can cause soil erosion in the upstream areas and potential flooding in the downstream area of the watershed. This study aims to determine the hydrology response based on watershed characteristics in terms of annual flow coefficient (AFC) and geomorphology. Geospatial hydrological modeling was built to assess hydrological characteristics using the SWAT (Soil and Water Assessment Tool). The analysis utilized primary data from field surveys and secondary spatial data, including geological maps, DEM, land use, soil, and daily rainfall, from 2013 to 2022. The study area covers the Raya Watershed in West Kalimantan. It was found in the Raya Watershed that open land use is prominent, with slopes ranging from sloping to steep in the upstream areas. The type of soil generally had porosity that did not support water absorption. These conditions caused more rainfall to be discharged as surface flow than absorbed into the soil. The AFC value during the study period ranged from 0.36 to 0.45, indicating a moderate hydrological response. Thus, groundwater storage in the watershed was very low. Consequently, the hydrological response of the watershed is unable to function optimally in its current condition. To overcome these problems, land conservation strategies, reforestation, and rehabilitation of old mine fields in upstream sub-basins are needed to reduce runoff and improve the watershed's ability to maintain a sustainable water balance.